2013
DOI: 10.1002/cphc.201300915
|View full text |Cite
|
Sign up to set email alerts
|

Radiation‐Induced Synthesis of Nanostructured Conjugated Polymers in Aqueous Solution: Fundamental Effect of Oxidizing Species

Abstract: Synthesis of conjugated poly(3,4-ethylenedioxythiophene) (PEDOT) polymers is achieved through the radiolysis of N2O-saturated aqueous solutions of 3,4-ethylenedioxythiophene by using two different oxidizing species: HO(·) (hydroxyl) and N3(·) (azide) radicals. Both oxidative species lead to self-assembled polymers that are evidenced in solution by cryotransmission electron microscopy and UV/Vis absorption spectroscopy and, after centrifugation and deposition, by scanning electron microscopy and attenuated tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 52 publications
9
35
0
Order By: Relevance
“…As observed, the prepared EDOT solution exhibits two absorption maxima at 242 and 259 nm which are features of the p-p* electronic transitions in the thiophene rings within the dichloromethane solvent. 16 This is consistent with the fact that pure thiophene molecules absorb light in the UV region between 225 and 245 nm, this absorption being ascribed to the p-p* transition. 30 Within this context, EDOT showed good solubility in dichloromethane which is higher than 20 mM in concentration (results not shown).…”
Section: Radiation Induced Synthesis Of Pedot and Dose Effect Studysupporting
confidence: 82%
See 2 more Smart Citations
“…As observed, the prepared EDOT solution exhibits two absorption maxima at 242 and 259 nm which are features of the p-p* electronic transitions in the thiophene rings within the dichloromethane solvent. 16 This is consistent with the fact that pure thiophene molecules absorb light in the UV region between 225 and 245 nm, this absorption being ascribed to the p-p* transition. 30 Within this context, EDOT showed good solubility in dichloromethane which is higher than 20 mM in concentration (results not shown).…”
Section: Radiation Induced Synthesis Of Pedot and Dose Effect Studysupporting
confidence: 82%
“…The absence of these bands after irradiation implies the formation of PEDOT polymers thanks to a,a 0 -coupling reactions. 16 The infrared spectra obtained after irradiation reveal the typical bands of the PEDOT polymers. Nevertheless, one can note the presence, whatever the irradiation dose, of a less common infrared band located at 1640 cm À1 .…”
Section: Radiation Induced Synthesis Of Pedot and Dose Effect Studymentioning
confidence: 99%
See 1 more Smart Citation
“…As observed, apparently such microstructure results from the assembly of lamellar architectures, suggesting that PHMeDOT organizes according to a foldedchain model. 50 Moreover, SEM cross section images (Figure 4d) demonstrate that the conductive…”
mentioning
confidence: 96%
“…Lee et al [85] reported the synthesis of highly uniform PPy particles (100~500 nm in diameter) with a good electrical property by in-situ γ-irradiation/induced chemical oxidative polymerization method. Remita et al [86,87] did a systematical investigation on radiolytic synthesis of PEDOT nanostructures and related mechanism.…”
Section: Other Approachesmentioning
confidence: 99%